Adhesion enhancement for nickel layer deposited on carbon fiber reinforced polymer (CFRP) composites by pretreatment processes for lightning strike. Issue 7 (19th May 2023) - Wu, Wangping; Xie, Dingkai; Huang, Jiaqi; Wang, Qinqin; Chen, Qing; Huang, Junjun
ABSTRACT: Carbon fiber-reinforced polymer (CFRP) is an engineering composites with excellent performance. The adhesion strength of nickel layer on CFRP composite was enhanced by pretreatment processes, including sandblasting and activation. The surface roughness, wettability, phase and microstructure of the CRFP and the layer were determined by surface profile-meter, goniometer, X-ray diffraction and scanning electronic microscopy, respectively. The adhesion force of nickel layer on CFRP composite was estimated by 3 M tape and pull-out test. The results showed that electroless nickel layer was composed of crystalline phase with small grain size, which belonged to medium-phosphorus deposits. The sandblasting improved the surface roughness and wettability of CFRP surface and rendered hydrophobic surface hydrophilic. The surface roughness of CFRP composites after sandblasting was enhanced by about 60.2%, at the same time the adhesion strength of the layer metalized CFRP composites after sandblasting was improved by 131%. After 3 M tape test, the adhesion state of nickel-CFRP composites with and without sandblasting could be qualitatively classified as grade 5B and 1B, respectively. The good adhesion of nickel layer on CFRP composite was generated from the increase in the surface roughness of CFRP composites after sandblasting and chemical activation, resulting in hydrogen bonds and covalent bonds. The lightning strike test showed that electroless nickel layer did not provide sufficient protection for the sandblasted CFRP composite when subjected to an big impulse current of up to 40 kA current peak and 8–20 μs duration due to the high electrical resistivity.